An Overview of Digital Media Literacy in Digital Bangladesh - Hossain, Barek; Fatima, Mobassera Jahan; Muzykant, Valerii L.; Hoesin, Cut Fitri Indah Sari; Nahiduzzaman, Md (Jurnal Cita Hukum, 2023)
The emergence of Web 2.0 has had an immense impact on the worldwide communication system, including the media. Therefore, traditional media outlets have shifted their focus exclusively to digital platforms. As a blessing of the rise of social media platforms, presses have been able to disseminate information swiftly, solicit reader criticism, and engage in two-way contact. However, gaining literacy, media, and digital media literacy competencies are crucial to benefiting from these information technologies. Besides, by acquiring these literacy skills, citizens of a developing country such as Bangladesh can significantly impact that country's Sustainable Development Goals (SDGs). Moreover, these competencies can help a country's citizens be more aware of fake news, misinformation, disinformation, and malformation. In this regard, the main objective of this article is to give an overview of digital media literacy in Bangladesh. For this purpose, the secondary data analysis method has been used to shed light on the digital inclusion process and development of information and communication technologies (ICT) in Bangladesh. Also, a literature review has been conducted on existing research on digital media literacy in the country. Finally, this research concluded that although the digital Bangladesh process has achieved great success in the short term, the supply of reasonable access to ICT for all the country's citizens will need more time. Thus, Bangladesh's government and non-government organizations and citizens need to go the extra mile to minimize this digital divide. Therefore, some potential components considered in the digital divide are citizens' position in rural vs. urban areas, literacy and income status gaps, and age range.